BOWLING MATHEMATIC GAME TO IMPROVE BEGINNING CALCULATING ABILITY OF CHILDREN 5-6 YEARS OLD - Fitri, Ruqoyyah; Alifia, Aulia Salma (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this research is to improve the initial numeracy skills for children aged 5 to 6 years through bowling mathematics games through class action methods with the Kemmis and MC Taggart models. Data was collected through observation sheets and analyzed through simple descriptive statistics. The subjects of this study were 25 children aged 5 to 6 years and the results concluded that the percentage of completeness on the indicator mentioned the pre-action number symbol was 48%, cycle 1 was 60% and cycle 2 was 87%, counting pre-action objects was 40%, 55% in cycle 1 and 84% in cycle 2, then using numbers to calculate pre-action by 28%, cycle 1 by 43% and cycle 2 by 81%. These results can be concluded that the bowling mathematics game can improve the ability of children aged 5 to 6 years in starting arithmetic.